Intrapulpal venous injection. Pilot study - A. Zh. Petrikas; E. V. Chestnykh; D. V. Medvedev; I. O. Larichkin; K. V. Kulikova (Эндодонтия Today)
Relevance. The reason for the study was our histological specimen with intrapulpal dye injection from the monograph "Anesthesia in Endodontics". Outside the pulp chamber, in the root canal, the ink is diffusely distributed throughout the vessels. There was a hypothesis about the vascular nature of intrapulpal injection.Aim. Тo prove vascular mechanism intrapulpal injection.Materials and methods. A randomized prospective pilot study was performed in 15 patients (9 men, 6 women) with 15 teeth vital pulpectomy. Traditional anesthesia conducted articaine 4% with epinephrine 1:100 000. When accessed in the pulpintroduced drop the same anesthetic. Heart rate was determined after 30 seconds for 3 minutes pulse oximeter MD 300.Results. There was expressed vascular reaction to intrapulpal introduction anesthetic with epinephrine. It has resulted in a sharp increase in pulse rate by an average of 11.3 beats /min, return to the original level after 3 minutes. Conclusions. Based on the results obtained, we assume the vascular-venous nature of intrapulpal anesthesia.